Assessing long-term conservation of groundwater resources in the Ogallala Aquifer Region using hydro-agronomic modeling - Xiang, Zaichen, author; Bailey, Ryan T., advisor; Niemann, Jeffrey, committee member; Bhaskar, Aditi, committee member; Suter, Jordan, committee member (Colorado State University. Libraries, 2022)
Groundwater is vital for domestic use, municipalities, agricultural irrigation, industrial processes, etc. Over the past century, excessive groundwater depletion has occurred globally and regionally, notably in arid and semi-arid regions, often due to providing irrigation water for crop cultivation. The High Plains Aquifer (HPA) is the largest freshwater aquifer in the United States and has experienced severe depletion in the past few decades due to excessive pumping for agricultural irrigation. There is a need to determine management strategies that conserve groundwater, thereby allowing irrigation for coming decades, while maintaining current levels of crop yield within the context of a changing climate. Numerical models can be useful tools in this effort. Hydrologic models can be used to assess current and future storage of groundwater and how this storage depends on system inputs and outputs, whereas agronomic models can be used to assess the impact of water availability on crop production. Linking these models to jointly assess groundwater storage and crop production can be helpful in exploring management practices that conserve groundwater and maintain crop yield under future possible climate conditions. The objectives of this dissertation are: i) to develop a linked modeling system between DSSAT, an agronomic model, and MODFLOW, a groundwater flow model to be used for evaluating long-term impacts of climate and management strategies on water use efficiency and farm profitability of agricultural systems while managing groundwater sustainably; ii) to use the DSSAT-MODFLOW modeling system in a global sensitivity analysis framework to determine the system factors (climate, soil, management, aquifer) that control crop yield and groundwater storage in a groundwater-stressed irrigated region, thereby pointing to possibilities of efficient management; and iii) to quantify the effect of groundwater conservation strategies and climate on crop yield and groundwater storage to identify irrigation and planting practices that will maintain adequate crop yield while minimizing groundwater depletion. These three objectives are applied to the hydro-agronomic system of Finney County, Kansas, which lies within the HPA. Major findings include: 1) climate-related parameters significantly affect crop yields, especially for maize and sorghum, and soybean and winter wheat yields are sensitive to a combination of cultivar genetic parameters, soil-related parameters, and climate-related parameters; 2) Climatic parameters account for 44%, 29%, 40%, and 36% variation in yield of maize, soybean, winter wheat, and sorghum; 3) Hydrogeologic parameters (aquifer hydraulic conductivity, aquifer specific yield, and riverbed conductance) have a relatively low influence on crop yields; 4) water table elevation, recharge, and irrigation pumping are considerably sensitive to soil- and climate-related parameters, while ET, river leakage, and groundwater/aquifer discharge are highly influenced by hydrogeological parameters (e.g., riverbed conductance, and specific yield); 5) the best management practice is the combination of implementing drip irrigation and planting quarter plots under both dry and wet future climate conditions. Other irrigation systems (sprinkler) and planting decisions (half-plots) can also be implemented without severe groundwater depletion. If crop yield is to be maintained in this region of the HPA, groundwater depletion can be minimized but not completely prevented. Results highlight the need for implementing new irrigation technologies, and likely changing crop type decisions (e.g., limiting corn cultivation) in coming decades in this region of the HPA. Results from this dissertation can be used in other groundwater-irrigated regions facing depletion of groundwater.